Preservation of Tolaki Mekongga Language Through Merdeka Curriculum-Based Local Subject Teaching Modules - Halil, Nur Ihsan; Arafah, Burhanuddin; Saputra, I Gede Purwana Edi; Hasyim, Ray Suryadi; Sarmadan; Takwa; Karma, Rudi (Journal of language teaching and research, 2024)
To expedite the implementation of the "Merdeka Curriculum," the government of North Kolaka District has established a policy regarding the subject of local language to show the identity of the Tolaki Mekongga community. However, this policy has not yet been realized in the form of teaching modules, particularly at the elementary school level. This research aims to create a teaching module based on the "Merdeka Curriculum" that accommodates the learning of the Tolaki Mekongga language at the elementary school level in North Kolaka District, Province of Southeast Sulawesi, Indonesia. This study employs a developmental research approach using the ASSURE model. This study's trial subjects (users) are teachers and students from SDN 3 Lambai, SDN 5 Kodeoha, and SDN 8 Kodeoha in North Kolaka District. Data were collected through expert validation and user trial questionnaires (teachers and students). The data of the research were processed and analyzed descriptively. The validation test results scored 83%, meeting the validity and suitability criteria. The user trial results (teachers and students) gained a score of 85%, meeting the practicality criteria. Therefore, the module resulting from this research is considered appropriate and practical for use in teaching the local subject of the Tolaki Mekongga language at the elementary school level in North Kolaka District.